Palladium-Loading Ceramic Catalytic Membrane Reactors for Mizoroki–Heck Reaction - Zhang, Fei; Zhou, Yong; Wang, Shuangqiang; Zhao, Yao; Wu, Xiaojin; Chen, Rizhi (Synthesis, 2023)
The general and efficient palladium-loading ceramic catalytic membrane reactor has been first reported to apply in the Mizoroki–Heck reaction. The as-fabricated catalytic membrane Pd-KH792-CM has shown high activity and selectivity in the flow-through Mizoroki–Heck reactions. The consistently high activity of the catalytic membrane in the five cycles has also proved its good stability and recyclability. Synthesis of drug molecules has further demonstrated that the catalytic membrane protocol is a powerful and comprehensive alternative to the traditional Mizoroki–Heck cross-coupling.
Keywords: catalytic membranes; Mizoroki–Heck reaction; flow-through catalytic membrane reactor; drug synthesis; heterogeneous catalysis